Pollution blamed for lower crop yields - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
Ozone, which is produced in the large cities of the South as well as the North, is spreading to rural areas and reducing' crop yields. The effect is probably made worse by high temperatures. These findings are revealed by research at Imperial...